Modelagem eletrotérmica e caracterização de elementos parasitas de placas de circuito impresso de conversores estáticos CC/CC - Piovesan, Tális (2021)
This doctoral thesis presents the development of an analythical method to characterize the parasitic elements and surface temperatures in a synchronous boost power converter. Initially is presented the bibliography review punctuating the inherent challenges and scientific researches developed in the power electronics research field in the evolution of DC/DC power conconverters design, like power density, switching frequency, efficiency and reliability increasing. From this point further study on high frequency power converters is made, highlighting power losses and negative effects which occur in the electrical circuit. Furthermore, are evaluated the impacts of the power converter PCB layout in the definition of parasitic elements and the thermal behavior of the constituent elements. After building the theoretical foundation is developed an analythical method which quantifies the parasitic elements and the surface temperature of the main power converter elements in a synchronous boost before its prototyping process in two distinct PCB layouts, with different surface area, cooper thickness, PCB thickness and pcb path dimensions. The analythical method was validated through experimental measurements in two physical prototypes and FEA simulation developed with Ansys Icepak and Ansys Q3D softwares. The obtained results are satisfactory and provide and improvement to the state of the art of high power density and efficient power converters design.